Code switching in the ESL classroom: the multilingual students’ perspectives - Johan Severinus Tati; Suthagar Narasuman; Wong, Jane Kong Ling (Pusat Penataran Ilmu Bahasa, Universiti Malaysia Sabah, 2020)
Code switching has become a common phenomenon ESL classroom where multilingualism is the norm. It is an evitable especially in Sabah Malaysia where multilingual learners are predominantly occupying the classrooms. Although, the method and techniques of English language teaching are consistently transformed, but the potential role of code switching is worth to be considered. This study is driven by the three objectives. First, to investigate the reasons to code switch. Second, it investigates the frequency of code switching and third to investigate the multilingual students’ perception on the use of code switching in the ESL classroom. The qualitative research approach was used to collect data from ten students of a community college in Sabah via the interview method. The findings of this study indicated that these students had a positive perception regarding code switching and they were using it to translate meaning from English to Malay or Sabah Malay dialect (SMD). In terms of frequency to code switch, the students asserted that they ‘always’ code switched in the ESL classroom. Malay or Sabah Malay dialect (SMD) was the domain language used in code switching. The students, perceived code switching as an alternative interaction tool and benefited from the intermittent use of other languages during the ESL classes. It is considerable to allow code switching in the multilingual classroom to develop the students ‘speaking confidence. Further research is recommended to explore the practice of code switching among the multilingual speakers in different domains such as home, work, and enterprising in Sabah.